Relações afetivas no trabalho: um estudo com profissionais da Enfermagem hospitalar - TALITA VANESSA AKAMINE DA SILVA (2024)
The interest of this dissertation is centered on studies on affective relationships at work, resulting from research with nursing professionals from a private hospital in Campo Grande (MS). As an epistemological basis, the Critical Theory of Society – Frankfurt School was used. This research had the specific objectives (1) the identification of the meaning given to work by the participants of this study and (2) the analysis of the emotions and affections expressed at work by the research participants. This research is qualitative in nature, through interviews with semi-structured questions organized according to the Social and Affective Relationships at Work Scale and subdivided into three subscales: work and ideology, affect and work and meaning of work – material developed and validated by Meneses (2008). The results obtained indicate that the research subjects identified work as meaningful, linked to supporting themselves and their family; feeling important, through professional choice (nursing- helping others) and usefulness (feeling useful). Regarding affections at work, research participants expressed happiness, anger and sadness. When expressing emotions, crying, anxiety, upset and stress were the main ones linked to work.